The In Vitro–In Vivo Safety Confirmation of PEG-40 Hydrogenated Castor Oil as a Surfactant for Oral Nanoemulsion Formulation - Rachmawati, Heni (Sci Pharm, 2017)
Evaluation on the safety use of high concentration of polyoxyl 40 (PEG-40) hydrogenated castor oil as a surfactant for oral nanoemulsion was performed in Webster mice. As previously reported, nearly 20% of PEG-40 hydrogenated castor oil was used to emulsify the glyceryl monooleate (GMO) as an oil to the aqueous phase. Thermodynamically stable and spontaneous nanoemulsion was formed by the presence of co-surfactant polyethylene glycol 400 (PEG-400). Standard parameters were analyzed for nanoemulsion including particle size and particle size distribution, the surface charge of nanoemulsion, and morphology. To ensure the safety of this nanoemulsion, several cell lines were used for cytotoxicity study. In addition, 5000 mg/kg body weight (BW) of the blank nanoemulsion was given orally to Webster mice once a day for 14 days. Several parameters such as gross anatomy, body weight, and main organs histopathology were observed. In particular, by considering the in vivo data, it is suggested that nanoemulsion composed with a high amount of PEG-40 hydrogenated castor oil is acceptable for oral delivery of active compounds.